PENGARUH TERPAAN MEDIA SOSIAL AKUN INSTAGRAM @NASARIASTRI TERHADAP KEBUTUHAN INFORMASI DALAM GAYA BERPAKAIAN WANITA BERHIJAB - Latifah (2023)
Data related to the high number of social media Instagram active users in Indonesia cannot be separated from the audience's reasons for obtaining information and inspiration. There are quite a lot of social media Instagram accounts that are used especially by women who wear hijab to find inspiration nowadays, because they're still find it difficult to mix and match clothes on a daily basis. Astri Rantasari as a fashion hijab influencer who consistently shares her fashion style as an inspiration through her Instagram account, @nasariastri. This study aims to identify how much influence social media exposure has on @nasariastri Instagram account on the need for information in fashion style of women wearing hijab. The study used the Uses and Gratification Theory by Elihu Katz, with 5 assumption of the information needs, that is: Cognitive Needs, Affective Needs, Individual Integrative Needs, Social Integrative Needs, and Escapism Needs. Researchers used a quantitative with explanative analysis method approach and data collection technique through questionnaire which are distributed to @nasariastri's followers with a total sample of 100 respondents. Broadly speaking, the way Astri Ratnasari packed her contents and the message in it can fulfill the 5 of information needs. Based on the research results, researchers draws the conclusion that there is a significant influence related to the social media exposure of the Instagram account @nasariastri on the need for information in fashion style of women wearing hijab.